2020
DOI: 10.3390/geosciences10040131
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Landslide Risk Assessment at Phuentsholing, Bhutan

Abstract: Landslides are one of the most destructive and most recurring natural calamities in the Himalayan region. Their occurrence leads to immense damage to infrastructure and loss of land, human lives, and livestock. One of the most affected regions is the Bhutan Himalayas, where the majority of the landslides are rainfall-induced. The present study aims to determine the hazard and risk associated with rainfall-induced landslides for the Phuentsholing region located in the southwestern part of the Bhutan Himalayas. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 44 publications
0
36
0
Order By: Relevance
“…Although the Nepal region saw a major earthquake in 2015, such a disastrous event in Bhutan has not occurred in the last century owing to variations in the segments of the Himalayas. These segments of Himalaya have divergent topography, geology and earthquake patterns [2]. There is a widespread belief that major earthquakes would not strike in Bhutan; however, it was reported that a major earthquake greater than a magnitude of 8 occurred in May 1713 which left in its wake widespread infrastructural damage and a staggering loss of human life.…”
Section: Introductionmentioning
confidence: 99%
“…Although the Nepal region saw a major earthquake in 2015, such a disastrous event in Bhutan has not occurred in the last century owing to variations in the segments of the Himalayas. These segments of Himalaya have divergent topography, geology and earthquake patterns [2]. There is a widespread belief that major earthquakes would not strike in Bhutan; however, it was reported that a major earthquake greater than a magnitude of 8 occurred in May 1713 which left in its wake widespread infrastructural damage and a staggering loss of human life.…”
Section: Introductionmentioning
confidence: 99%
“…the Langtang Valley (Jones et al, 2019). Although forest coverage of >60% is prescribed by the Bhutanese constitution, and most of the outcropping rocks are harder rocks of the Greater Himalayan Series, there are areas of weaker geology where landslides are a serious risk (Dikshit et al, 2020). In Bhutan this is highly critical as the road network resembles a fishbone with very few, to no alternative routes from the main east-west highway, and helicopter landing spots are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…In the geological parameters, we divide by formation using porosity, sorting, mineral content, and density of joints considerations. Vegetation parameters are classified based on the presence of vegetation (Dikshit et al, 2020). Slope and Elevation is classified into 5 classes from <15 to > 45 for slope (Bijukchhen et al, 2012); and <0 to >1000 for elevation (Chen et al, 2014).…”
Section: Landslide Hazard Assessmentmentioning
confidence: 99%
“…After that, we use the WLC method using these 4 parameters to make a Landslide Vulnerability Assessment Map (Figure 7.). Vulnerability map is divided into five classes: Very Low (0-0.36), Low (0.37-0.48), Moderate (0.49-0.64), High (0.65-0.76), and Very High (0.77-1) (Dikshit et al, 2020). The maps derived using both the components resulted in the Vulnerability map.…”
Section: Landslide Vulnerability Assessmentmentioning
confidence: 99%